Consistent testing for stochastic dominance: A subsampling approach - Oliver Bruce Linton; Esfandiar Maasoumi; Yoon-Jae Whang (Centre for Microdata Methods and Practice (cemmap), 2003)
We propose a procedure for estimating the critical values of the extended Kolmogorov- Smirnov tests of First and Second Order Stochastic Dominance in the general K-prospect case. We allow for the observations to be serially dependent and, for the first time, we can accommodate general dependence amongst the prospects which are to be ranked. Also, the prospects may be the residuals from certain conditional models, opening the way for conditional ranking. We also propose a test of Prospect Stochastic Dominance. Our method is based on subsampling and we show that the resulting tests are consistent and powerful against some N-1=2 local alternatives. We also propose some heuristic methods for selecting subsample size and demonstrate in simulations that they perform reasonably.
Keywords: 330; Präferenztheorie; Theorie; Bootstrap-Verfahren